Application status and thinking of Traditional Chinese Medicine nursing technology in community-based nursing (中医护理技术在社区护理中的应用现状及思考) - ZHANG Lijun (张丽君); CAO Lei (曹蕾); E haiyan (鄂海燕); TANG Ling (唐玲); ZHEN Naihua (郑乃花) (中西医结合护理, 2022)
Traditional Chinese Medicine(TCM) nursing technology has unique advantage in life cultivation and health preservation, chronic disease management and other areas. The community nurses’ awareness of TCM nursing technology remains to be improved. There is an increasing need for TCM nursing among community dwellers in China. However, the promotion and practice of TCM nursing technology provided by community nurses are influenced by the inconsistent standards of medical costs, level of community-based nursing service and other issues. This paper briefly summarized the Application status and thinking of TCM nursing technology in community nursing, in order to provide reference for the community-based promotion and practice. (中医护理技术在养生保健、慢性病康复管理等方面有着独特的优势。社区护理人员对中医护理技术的认知有待提高。社区居民对中医护理技术的需求高, 但受限于相关收费标准尚未统一、基层护理人员技能水平参差不齐等, 中医护理技术依托社区工作人员的应用及推广工作仍面临多重困难。本文简要概述了中医护理技术在社区护理中的应用现状, 并提出相关思考, 旨在为中医护理技术的推广提供参考。)